Extraconal cavernous hemangioma of orbit: A case report - Anand, Rama (Medknow Publications, 2008)
Cavernous hemangioma is the most common benign noninfiltrative neoplasm of the orbit. Most cavernous hemangiomas are intraconal and lateral in location. We present a case of a cavernous hemangioma with an unusual extraconal and superomedial location.